The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4081/aiua.2014.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic utility of transrectal ultrasound in urological office prostatic abscess management: A short report from a single urologic center

Abstract: TRUS evaluation in case of persistent LUTS associated with fever or acute urinary retention is determinant in the diagnosis of PA. Office or institutional management with TRUS needle aspiration is a good option in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…TRUS is the most common and inexpensive method available, providing an accurate diagnosis in 80–100% of patients . This technique is preferable to transperineal or transabdominal ultrasound, as TRUS involves direct contact with the prostate and resolution by intervening surfaces is not limited.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…TRUS is the most common and inexpensive method available, providing an accurate diagnosis in 80–100% of patients . This technique is preferable to transperineal or transabdominal ultrasound, as TRUS involves direct contact with the prostate and resolution by intervening surfaces is not limited.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…20 S. aureus remains the most common hematogenously spread infection leading to PA. Increasing cases as a result of MRSA, both nosocomial and community-acquired, [35][36][37] are a growing concern, with >30 cases of PA as a result of S. aureus (methicillin-resistant and -sensitive) reported in the literature. 38 Other reported bacterial pathogens include Klebsiella pneumoniae, [39][40][41] Enterococcus species, 34,42,43 Streptococcus species, 44 Pseudomonas aeruginosa, 45 Bukholderia pseudomallei [46][47][48] and Brucella melitensis. 49 Atypical organisms are seen more frequently in the severely immunocompromised, such as post-transplant and AIDS patients, 18 and include pathogens seen at a higher incidence in those populations, such as mycobacteria (Mycobacterium avium intracellulare, mTB 50,51 ), as well as pathogenic fungi, such as Coccidioides immitis, 52 Candida species, [53][54][55] Cryptococcus neoformans, 20,56 Blastomyces dermatitidis, 57 Histoplasma capsulatum 58,59 and Cladophialophora carrionii.…”
Section: Causative Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital rectal examination (DRE) is the cornerstone of PA clinical diagnosis with fluctuance or 'bogginess' being almost pathognomic of PA. One study found that fluctuation on DRE was present in 83% of patients with PA confirmed by ultrasound, 22 though other studies put the figure much lower at between 29-43%. [23][24][25] Prostate-specific antigen (PSA) values are also likely to be raised.…”
Section: Risk Factors and Associationmentioning
confidence: 99%
“…It has the benefit of offering both diagnostic and therapeutic opportunities and has been found to be the most reliable method to diagnose the condition, providing an accurate diagnosis in between 80-100% of cases. 16,[23][24][25] Abscesses are hypoechoic and well defined on ultrasound scans. There may be internal septa or heterogeneous solid portions.…”
Section: Trans-rectal Ultrasoundmentioning
confidence: 99%